Cognitive impairment and associated factors among patients with diabetes mellitus in Africa: a systematic review and meta-analysis - Chekol Tassew, Worku; Ferede, Yeshiwas Ayal; Zeleke, Agerie Mengistie (Frontiers in Endocrinology, 2024)
Background Inappropriate management of blood sugar in patients with diabetes mellitus leads to micro-vascular and macro-vascular complications, subsequently leading to high morbidity and mortality rates. In addition, diabetes independently increases the occurrence of cognitive impairment complicated by dementia. Scientific evidence on the magnitude of cognitive impairment will provide a sound basis for the determination of healthcare needs and the planning of effective healthcare services. Despite this, there are no comprehensive data on the prevalence and associated factors of cognitive impairment among patients with diabetes in Africa. Methods To identify relevant articles for this review, we searched PubMed, Cochrane Library, Science Direct, African Journals Online, and Google Scholar. After extraction, the data were imported into Stata software version 11 (Stata Corp., TX, USA) for further analysis. The random-effects model, specifically the DerSimonian and Laird (D+L) pooled estimation method, was used due to the high heterogeneity between the included articles. Begg’s and Egger’s regression tests were used to determine the evidence of publication bias. Sub-group analyses and sensitivity analyses were also conducted to handle heterogeneity. Results The pooled prevalence of cognitive impairment among patients with diabetes in Africa is found to be 43.99% (95% CI: 30.15–57.83, p < 0.001). According to our analysis, primary level of education [pooled odds ratio (POR) = 6.08, 95% CI: 3.57–10.36, I2 = 40.7%], poorly controlled diabetes mellitus (POR = 5.85, 95% CI: 1.64–20.92, I2 = 87.8%), age above 60 years old (POR = 3.83, 95% 95% CI: 1.36–10.79, I2 = 63.7%), and diabetes duration greater than 10 years (POR = 1.13; 95% CI: 1.07–1.19, I2 = 0.0%) were factors associated with cognitive impairment among patients with diabetes. Conclusion Based on our systematic review, individuals with diabetes mellitus exhibit a substantial prevalence rate (43.99%) of cognitive impairment. Cognitive impairment was found to be associated with factors such as primary level of education, poorly controlled diabetes mellitus, age above 60 years, and diabetes duration greater than 10 years. Developing suitable risk assessment tools is crucial to address uncontrolled hyperglycemia effectively. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42024561484.